Five Years After the COVID-19 Pandemic: Old Problems and New Challenges in Forensic Pathology - Mario Chisari; Martina Francaviglia; Sabrina Franco; Gianpietro Volonnino; Raffaella Rinaldi; Nicola Di Fazio; Lucio Di Mauro (Forensic Sciences)
Background: The COVID-19 pandemic significantly disrupted forensic science, exposing vulnerabilities and introducing unprecedented challenges. Five years later, its impact persists, necessitating ongoing adaptations in forensic practice. This study examines key transformations, persistent issues, and emerging challenges in forensic science post-pandemic. Methods: A critical analysis of forensic science’s response to the pandemic was conducted, focusing on operational disruptions, methodological advancements, educational shifts, and technological integration. Results: Forensic operations faced delays due to case backlogs, restricted in-person work, and postponed court proceedings. Forensic pathology evolved with increased reliance on molecular autopsy techniques to clarify COVID-19-related deaths. Educational methods shifted toward virtual learning, prompting discussions on standardized digital training. Additionally, artificial intelligence and automation gained prominence in forensic investigations, enhancing crime scene analysis and predictive modeling. Discussion: While forensic science demonstrated adaptability, challenges remain in international collaboration, resource distribution, and professional training. The pandemic accelerated technological integration but also raised ethical and procedural concerns, particularly regarding AI applications in legal contexts. Virtual learning innovations necessitate further development to ensure competency in forensic training. Conclusions: Forensic science continues to evolve in response to post-pandemic realities. Addressing gaps in cooperation, technology implementation, and training will be crucial to strengthening the field. By assessing these changes, this study underscores forensic science’s resilience and adaptability, offering insights into its future trajectory amid ongoing challenges.